Traumatic events, post-migration living difficulties and post-traumatic symptoms in first generation immigrants: a primary care study - Massimiliano Aragona; Daniela Pucci; Marco Mazzetti; Bianca Maisano; Salvatore Geraci (Istituto Superiore di Sanità, 2013)
OBJECTIVES: To study potentially traumatic events (PTE), post-traumatic stress disorder (PTSD), anxiety, depression, somatization and post-migration living difficulties (PMLD) in primary care immigrants. DESIGN: Patients self-rated transculturally validated questionnaires. Those with and without PTSD were compared on all variables. The influence of the number of PTE and of PMLD on PTSD was measured. RESULTS: 391 patients completed the questionnaires. Prevalence of PTSD was 10.2%. PTE and PMLD were frequent in the whole sample but more common in PTSD subjects. Either the number of PTE and of PMLD significantly increased the likelihood to have a PTSD. CONCLUSIONS: PTE, PMLD, PTSD and related conditions (anxiety, depression and somatization) are frequent among immigrants in primary care, and either PTE and PMLD significantly influence resulting psychopathology. The implications in clinical practice are discussed.